Note about 50th anniversary - R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
This year marks the 50th Swine Industry Day and Report of Progress. We are deeply appreciative of the innovators who had the foresight to begin such a program of disseminating the latest swine research to the industry and the many people who have contributed along our 50-year history. K-State’s Swine Day is the oldest and longest-running swine day in the country. It provides us the opportunity to share the latest research with our K-State family, and could not have been done without the tremendous support of our producers, industry stakeholders, and students.
Keywords: swine